2018
DOI: 10.1111/1755-6724.13689
|View full text |Cite
|
Sign up to set email alerts
|

Controls of Acid‐sensitive Minerals on Reservoir Sensitivity Testing: An Example from the Silurian Kepingtage Formation in Tazhong Area, Tarim Basin

Abstract: The Silurian Kepingtage Formation in Tazhong area is regarded as an acid‐sensitive hydrocarbon reservoir. However, formation mechanism of acid‐sensitive of the reservoir cannot be interpreted by the existing acid‐sensitive evaluation criterion based on damage rate. The contents of acid ‐sensitive minerals illustrated by bulk‐rock XRD, scanning electron microscopy and clay mineral composition analysis exert the dominant control on acid‐sensitive flow testing of the reservoir. The iron‐ bearing minerals (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In terms of AEP, Liao et al [ 31 ] explored the feasibility of permeability improvement of acid-rock reaction by the indoor plunger experiment and found that the acidic fluid systems (including hydrochloride acid, formic acid and acetic acid) can significantly improve the core permeability with an average percentage increase of 763 %. Han et al [ 37 ] investigated the influence of iron-bearing minerals and iron-free minerals on the reservoir permeability and provides theoretical guidance for the application of AEP. Sun et al [ 38 ] further studied the internal mechanism of acid-rock reaction on the reservoir permeability, the enlarged small and large pores/throats induced by the chemical corrosion contributed to the permeability enhancement of reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of AEP, Liao et al [ 31 ] explored the feasibility of permeability improvement of acid-rock reaction by the indoor plunger experiment and found that the acidic fluid systems (including hydrochloride acid, formic acid and acetic acid) can significantly improve the core permeability with an average percentage increase of 763 %. Han et al [ 37 ] investigated the influence of iron-bearing minerals and iron-free minerals on the reservoir permeability and provides theoretical guidance for the application of AEP. Sun et al [ 38 ] further studied the internal mechanism of acid-rock reaction on the reservoir permeability, the enlarged small and large pores/throats induced by the chemical corrosion contributed to the permeability enhancement of reservoirs.…”
Section: Introductionmentioning
confidence: 99%